Blood lead concentration, renal function, and blood pressure in London civil servants. Issue 7 (July 1990) - Staessen, J; Yeoman, W B; Fletcher, A E; Markowe, H L; Marmot, M G; Rose, G; Semmence, A; Shipley, M J; Bulpitt, C J
Abstract : Blood lead concentration was measured in 398 male and 133 female London civil servants not subject to industrial exposure to heavy metals. The relation between blood lead and serum creatinine concentrations and blood pressure were examined. Blood lead concentration ranged from 0.20 to 1.70 mumol/l with a geometric mean concentrations of 0.58 mumol/l in men and 0.46 mumol/l in women (p less than 0.001). In women blood lead concentration increased with age (r = +0.27; p = 0.002). In the two sexes blood lead concentration was positively correlated with the number of cigarettes smoked a day (men r = +0.17 and women r = +0.22; p less than or equal to 0.01), with the reported number of alcoholic beverages consumed a day (men r = +0.34 and women r = 0.23; p less than 0.01), and with serum gamma-glutamyltranspeptidase (men r = +0.23 and women r = +0.14; for men p less than 0.01). Blood lead concentration was not correlated with body weight, body mass index, and employment grade. In men 14% of the variance of blood lead concentration was explained by the significant and independent contributions of smoking and alcohol intake and in women 16% by age, smoking, and alcohol consumption. In men serum creatinine concentration tended to rise by 0.6 mumol/l (95% confidence interval from -0.2 to +1.36 mumol/l) for each 25% increment in blood lead concentration. In men and women the correlations between blood lead concentration and systolic and diastolic blood did not approach statistical significance. In conclusion, in subjects not exposed to heavy metals at work gender, age, smoking, and alcohol intake are determinants of blood lead concentration. At a low level of exposure, lead accumulation may slightly impair renal function, whereas blood pressure does not seem to be importantly influenced. Alternatively, a slight impairment of renal function may give rise to an increase in blood lead concentration.